Impact of ICT Adoption on Inequality: Evidence from Indonesian Provinces - Harry Patria; Abdul Azeez Erumban (Pusbindiklatren Bappenas, 2020)
This study investigates the relationship between ICT adoption ratio and income inequality. While the majority studies explain the impact of ICT on income inequality via labor market, this study offers a different perspective on this relationship. The fast-growing ICT has influenced, not only the employment income, but also the household income, such as property income, consumer surplus, etc. Thus, this study seeks to show the impact of ICT on income inequality via household income channel. The large internet economy and the remarkable internet adoption increase in Indonesia demonstrate the considerable impact of ICT on the lives and income of people in Indonesia. By using panel data regression, this paper shows an inverted U-shape relationship between ICT adoption and income inequality. Low ICT adoption increased income inequality until a certain turning point, whereby higher ICT adoption reduced income inequality in society. The turning point relating to average adoption ratio of mobile phone, computer, and internet was 25%; while there was an average adoption ratio of 17% for computer and internet.